Вы находитесь на странице: 1из 6

Choose the most appropriate option (a, b, c or d).

n dy
Q 1. If y = (1 + x)(1 + x2)(1 + x4) … (1 + x2 ) then at x = 0 is
dx

(a) 1 (b) -1 (c) 0 (d) none of these

dy 2
Q 2. If y | cos x |  | sin x | then at x  is
dx 3

1 3 1
(a) (b) 0 (c) ( 3  1) (d) none of these
2 2

Q 3. The differential coefficient of f(logex) with respect to x, where f(x) = logex, is

x 1 1
(a) (b) loge x (c) (d) none of these
loge x x x loge x


Q 4. If f(x) = cos x. cos 2x cos 4x. cos 8x. cos 16x then f '   is
4

1
(a) 2 (b) (c) 1 (d) none of these
2

dy 5
Q 5. If y = cos1(cos x) then at x  is equal to
dx 4

1
(a) 1 (b) -1 (c) (d) none of these
2

dy
Q 6. If y = sec(tan-1x) then at x = 1 is equal to
dx

1 1
(a) (b) - (c) 1 (d) none of these
2 2

dy
Q 7. If xy = ex-y then at x = 1 is equal to
dx

(a) 0 (b) -2 (c) 1 (d) none of these

dy
Q 8. If xexy – y = sin2x then at x = 0 is
dx

(a) 0 (b) 1 (c) -1 (d) none of these

y ....to  dy
Q 9. If x  ey  e then is
dx
x 1 1 x
(a) (b) (c) (d) none of these
1 x x x

dy
Q 10. If y  log2 (loge x) then is
dx

1 1 1
(a) log2 e.logx e (b) log2 x (c) loge x (d) none of these
x x x

dy
Q 11. If f’(x) = 2x2  1 and y  f(x 2 ) then at x = 1 is
dx

(a) 2 (b) 1 (c) -2 (d) none of these

 5cos x  12sin x    dy
Q 12. If y  cos1   ;x   0,  , then is equal to
 13   2 dx

(a) 1 (b) -1 (c) 0 (d) none of these

x 1 dy
Q 13. If y  tan1 then is equal to
x 1 dx

1 1 1
(a) (b) (c) (d) none of these
2 | x | x 1 2
2x x  1 2
2x x 2  1

dy
Q 14. If xy . yx = 16 then at (2, 2) is
dx

(a) 1 (b) -1 (c) 0 (d) none of these

dy
Q 15. If y = x1/x, the value of at x = e is
dx

(a) 1 (b) 0 (c) -1 (d) none of these

2x 2x
Q 16. The derivative of tan-1 with respect to sin-1 is
1  x2 1  x2

1 1
(a) (b) (c) 0 (d) 1
1  x2 1  x2

Q 17. Let the function y = f(x) be given by x = t5 – 5t3 – 20t + 7 and y= 4t3 – 3t2 – 18t + 3, where t  (-2,
2). Then f’(x) at t = 1 is

5 2 7
(a) (b) (c) (d) none of these
2 5 5
   
Q 18. If f(x)  cos  [x]  x3  , 1 < x < 2, and [x] = the greatest integer ≤ x, then f '  3  is equal to
2   2

2/3 3/2
 
(a) 0 (b) 3   (c) 3   (d) none of these
2 2

dy
Q 19. If y = sin xo and x = cos x then is equal to
dz

 x
(a) –cosec x . cos x (b) cos ec .cos x
180 180

 x
(c)  cos ec.cos (d) none of these
180 180

1  x2  1
Q 20. The derivative of tan1 with respect to tan-1 x is
x

1  x2  1 1
(a) (b) 1 (c) (d) none of these
x2 1  x2

1 1
Q 21. The differential coefficient of cosec-1 with respect to 1 x2 at x  is
2x 2  1 2

(a) -4 (b) 4 (c) -1 (d) none of these

Q 22. If the prime sign(') represents differentiation w.r.t. x and f'(x) = sin x + sin 4x . cos x then
  
f '  2x 2   at x  is equal to
 2 2

(a) 0 (b) -1 (c) 2 2 (d) none of these

du
Q 23. If u = f(x3), v = g(x2), f'(x) = cos x and g'(x) = sin x then is
dv

3 2
(a) x.cos x3 .cosec x 2 (b) sin x 3 .sec x 2 (c) tan x (d) none of these
2 3

 2x  1 dy
Q 24. If y  f   and f '(x)  sin x then dx is
2

 x  1
2

2 2
 2x  1  2(1  x  x 2 )  2x  1 
(a) sin  2  (b) sin  2 
 x  1 (x  1)
2 2
 x  1

2
2(2x  1)  2x  1
(c) sin  2  (d) none of these
x2  1  x  1
1 t  1 t y 1 t dy 1
Q 25. If e x  and tan  then at t  is
1 t  1 t 2 1 t dx 2

1 1
(a)  (b) (c) 0 (d) none of these
2 2

dy
Q 26. If t(1  x 2 )  x and x 2  t 2  y then at x = 2 is
dx

88 488
(a) (b) (c) 1 (d) none of these
125 125

Q 27. Let f(x) be a polynomial function of the second degree. If f(1) = f(-1) and a1, a2, a3 are in AP then
f'(a1), f'(a1), f'(a3) are in

(a) AP (b) GP (c) HP (d) none of these

Q 28. If P(x) is a polynomial such that P(x2 + 1) = {P(x)}2 + 1 and P(0) = 0 then P'(0) is equal to

(a) 1 (b) 0 (c) -1 (d) none of these

 1  dy 
Q 29. If 5f(x) + 3f   = x + 2 and y = xf(x) then   is equal to
x  dx  x 1

7
(a) 14 (b) (c) 1 (d) none of these
8

Q 30. If for all x, y the function f is defined by

f(x) + f(y) + f(x) . f(y) = 1 and f(x) > 0 then

(a) f'(x) does not exist (b) f'(x) = 0 for all x (c) f'(0) < f'(1) (d) none of these

Q 31. There exists a function f(x) satisfying f(0) = 1, f'(0) = -1, f(x) > 0 for all x and

(a) f'(x) < 0 for all x (b) -1 < f"(x) < 0 for all x (c) -2 ≤ f"(x) ≤ -1 for all x (d) f"(x) ≤ -2 for all x

Q 32. If g is the inverse function of f and f'(x) = sin x then g'(x) is

1
(a) cosec {g(x)} (b) sin {g(x)} (c)  (d) none of these
sin{g(x)}

Q 33. Let f(x) be a polynomial function of degree 2 and f(x) > 0 for all x  R. If g(x) = f(x) + f'(x) + f"(x)
then for any x

(a) g(x) < 0 (b) g(x) > 0 (c) g(x)= 0 (d) g(x)  0
d  3 d2 y 
Q 34. If y 2  P(x) = a polynomial of degree 3 then 2 y  equals
dx  dx 2 

(a) P"'(x) + P'(x) (b) P"(x) . P"'(x) (c) P(x) . P"'(x) (d) none of these

x3 sin x cos x
Q 35. Let f(x)  6 1 0 ,
2
p p p3

d3
where p is a constant. Then {f(x)} at x = 0 is
dx3

(a) p (b) p + p2 (c) p + p3 (d) independent of p

d6 y 
Q 36. If y = sin 2x then 6
at x  is equal to
dx 2

(a) -64 (b) 0 (c) 64 (d) none of these

d2 x 
Q 37. x = t cos t, y = t + sin t then at t  is equal to
dy 2 2

4 4
(a) (b)  (c) -2 (d) none of these
2 2

d2 y 1
Q 38. If y = at2, x = 2at, where a is a constant, then 2
at x  is
dx 2

1
(a) (b) 1 (c) 2a (d) none of these
2a

Choose the correct options. One or more options may be correct.

Q 39. Let f(x) = (ax + b)cos x + (cx + d)sin x and f'(x) = x cos x be an identity in x. Then

(a) a = 5 (b) b = 1 (c) c = 1 (d) d = -5

2x
Q 40. Let f(x) = 2tan-1x + sin-1 . Then
1  x2

 1 16  1
(a) f '(2)  f '(3) (b) f'(2) = 0 (c) f '    (d) f '    0
2 5  2

Q 41. If f(x) = x3 + x2f'(1) + xf"(2) + f"'(3) for all x  R then

(a) f(0) + f(2) = f(1) (b) f(0) + f(3) = 0 (c) f(1) + f(3) = f(2) (d) none of these
Q 42. If f(x – y), f(x) . f(y) and f(x + y) are in AP for all x, y, and f(0)  0, then

(a) f(2) = f(-2) (b) f(3) + f(-3) = 0 (c) f'(2)+ f'(-2) = 0 (d) f'(3) = f'(-3)

Q 43 Let f(-x) = f(x). Then f'(x) must be

(a) an even function (b) an odd function (c) a periodic function (d) neither even nor off

d
Q 44. If fn(x) = e f n1 ( x )
for all n  N and f0 (x)  x then {fn (x)} is equal to
dx

d
(a) fn (x). {fn 1(x)} (b) fn (x).fn1(x) (c) fn (x).fn1(x). ... .f2 (x).f1(x) (d) none of these
dx

Q 45. Let f(x) = x2 + xg'(1) + g"(2) and g(x) = f(1) . x2 + xf'(x) + f"(x) then

(a) f'(1) + f'(2) = 0 (b) g'(2) = g'(1) (c) g"(2) + f"(3) = 0 (d) none of these

Answers
1a 2c 3c 4a 5b 6a 7a 8b 9c 10a

11a 12a 13a 14b 15b 16d 17b 18a 19c 20d

21a 22c 23a 24b 25a 26b 27a 28a 29b 30b

31a 32a 33b 34c 35d 36b 37b 38a 39bc 40abc

41abc 42ac 43b 44ac 45abc